ASSISTANCE FOR DYSLEXIC STUDENTS AS A STRATEGY TO IMPROVE THE QUALITY OF EDUCATION AT SDN 1 SELOREJO - Kartika Shafa; Ulil Fauziyah, M.HI; Sefyra Adienda Putri Pradani; Mar`atus Sholihah; Maski Isnaini Azizah; Sisca Fitria Dewi; Firman Kawah Insan (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Reading skills, which are basically the main capital in exploring knowledge as well as skills in students, are often overlooked or even ignored. Teachers and parents who realized this too late became the forerunners of the long tail of dyslexic students' problems, which also affected their scholastic skills. By conducting this research, the researchers hope that it will be possible to increase or at least improve the quality of life for the people of Dau village, especially the younger generation, and gain insight for parents and teachers in taking action regarding dyslexic students. This research used descriptive qualitative research. This research was conducted at SDN 01 Selorejo, Dau District, Malang Regency, East Java Province. The results of the study concluded that there were two factors that influenced the personalities of the students, namely internal factors and external factors. The most influential internal factors in the student learning process are motivation, interests, and attitudes. while the external factors are the school environment, family environment, and community environment.